Influência do tamanho do habitat e da cobertura de dossel sobre as teias tróficas da microbiota em fitotelmatas de Quesnelia arvensis (Bromeliaceae) - Leite, Edilaine Corrêa (2021)
The aquatic communities in phytotelmata are structured by several environmental factors, and they act in the trophic and non-trophic interactions of these environments. Phytotelmata are micro-ecosystems of fresh water, rich in species and are considered an excellent study model. Here, we use plants from the family Bromeliaceae of the species Quesnelia arvensis, to investigate the relationships between biotic and abiotic variables and their effects on interactions in phytotelmata. Our hypothesis was that habitat size and canopy cover gradients would determine the abundance of microbiota communities and their interactions. We carried out samples on bromeliads located in the state park of the Parque Estadual da Ilha do Cardoso - SP, Brazil, in different canopy cover gradients, in addition we selected plants of different sizes, to investigate the effects of habitat size. To check the interactions between the variables and score the interactions (positive and negative) we use the lasso graphical method, which exemplifies these interactions through a network graph. Also, we performed a simple regression analysis in to determine the correlations between biotic and abiotic variables. Our results indicate that the canopy cover and the size of the habitat (water volume) were the most important variables in interactions in phytothelmata. The canopy cover presented the greatest amount of negative connections, mainly with the levels of ammonia, Culicidae larvae and algae in general, with the exception of phyto-flagellates. In contrast, habitat size showed strong positive connections with rotifers and copepods and did not show any negative connection with other variables. Finally, our results demonstrate that among the set of factors analyzed, canopy cover and habitat size were in fact the most representative, as expected.